تأثير زيادة الوزن عند السيدات على صورة الجسم وتقدير الذات - دونا, عيسى عبود (Latakia University Journal -Medical Sciences Series, 2019)
على الرغم من أن صورة الجسد هي بنية معقدة والتي تضم الطريقة التي نرى بها أنفسنا، وطريقة تفكيرنا وشعورنا بأجسادنا، إلا أنه في المجتمع المعاصر أصبح المحور الرئيسي لصورة الجسم هو في وزنه. وهذا ليس مستغربا عندما نعلم أن النظرة المثالية للجمال الحالي للمرأة تؤكد على النحافة، و "النحافة تساوي الجاذبية". إن الصورة السلبية لصورة الجسم تؤثر سلباً على مستوى احترام الذات. حتى النساء اللواتي تبدون متأكدات جداً من أنفسهن يعترفن بوجود انخفاض احترام الذات وغالباً ما يجعلهن غير سعداء، وغير قادرات على القيام ببعض الأشياء التي تردن القيام بها، ويجري هذا النوع عند النساء اللواتي يردن تحقيق ذاوتهن. في هذه الدراسة نلاحظ أن 67 % من النساء ذوات الوزن الطبيعي كان تقدير الذات لديهن عال مقارنة مع 18 % من النساء البدينات. كذلك 96 % من ذوات الوزن الطبيعي كان لديهن نظرة عالية لصورة أجسامهن مقارنة مع 2 % من النساء البدينات. ونستنتج من ذلك أن السيدات البدينات يعانين من نقص تقديرهن للذات مقارنة مع السيدات غير البدينات إضافة إلى أنهن لديهن صورة سلبية تجاه أجسادهن. وأن تكوني ناجحة، ومحبوبة، ومتحفزة للحياة يسمح لك بتجنب الخوف والهوس من الوزن الزائد وإتباع نظام غذائي للمحافظة عليه. لذلك يجب أن تلقى المرأة التثقيف الصحي حول الأساليب التي تتحكم بوزن الجسم خلال حياتها. Although body image is a complex construct which includes all of how we see, think and feel about our whole bodies, in contemporary society the major focus has become on weight. This is not surprising when the current beauty ideals for women inordinately emphasize thinness, and “thinness equals attractiveness”. Negative body image affects negatively on the level of self-esteem. Even women who seem to be very sure of themselves will admit to having low self esteem that often makes them unhappy, keeping them from doing some of the things they want to do and being the kind of person they want to be. In this study, we notice that 67% of women with normal weight were self-esteem to have a high, compared with 18% of obese women. As well as 96% of women with normal weight had to have a look to the image of their bodies high compared with 2% of the obese women. It is therefore concluded that obese women suffered from low self-esteem and negative body image by comparison with normal women. To be successful, and loved, and eager to live is something that allows you to avoid fear and obsession with the extra weight and diet to maintain. Therefore, women should receive health education about the methods that control body weight through her ​​life.